Developing Partnership between National Bank of Romania and Universities - Ioana Florentina SAVU (Revista de Management Comparat International)
Since May 2009, National Bank of Romania (N.B.R.) initiated an educational project under the name „Open days for economists students”. The main objective of the project is improving knowledge and understanding, in the academic area, of the central bank activity, the role, functions and implications of its decisions in the romanian economy, thereby creating and strengthening channels of communication needed to ensure adequate financial education. The specific objectives of the operation aiming knowledge aspects of the European System of Central Banks, of the basics about the objectives and role of N.B.R in the Romanian economy, the strategy, the monetary policy and financial stability mechanisms. The target audience consists of students of economic faculties of major universities, school teachers and students of doctoral universities. In 2010, the project has developed in a new format, which took into account the experience gained, the signals received from participating students and teachers involved in running the pilot project initiated in 2009. The new format will be presented in the following article.